BROAD LIGAMENT HAEMATOMA FOLLOWING NORMAL VAGINAL DELIVERY - Ibrar, Faiza; Awan, Azra Saeed; Fatima, Touseef; Tabassum, Hina (Journal of Ayub Medical College Abbottabad, 2017)
A 37-year-old, patient presented in emergency with history of normal vaginal delivery followed by development of abdominal distention, vomiting, constipation for last 3 days. She was para 4 and had normal vaginal delivery by traditional birth attendant at peripheral hospital 3 days back. Imaging study revealed a heterogeneous complex mass, ascites, pleural effusion, air fluid levels with dilatation gut loops. Based upon pelvic examination by senior gynaecologist in combination with ultrasound; a clinical diagnosis of broad ligament haematoma was made. However, vomiting and abdominal distention raised suspicion of intestinal obstruction. Due to worsening abdominal distention exploratory laparotomy was carried out. It was pseudo colonic obstruction and caecostomy was done. Timely intervention by multidisciplinary approach saved patient life with minimal morbidity. Keywords: Broad ligament; haematoma; pseudo intestinal obstruction; caecostomy